Luis Antonio de Villena: from the great style to the realism - Picardo, Osvaldo M. (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
I have resorted to several theoretic notions that had permited me to develop the thesis of the present article: the institutionalization of a contractual relation between writer and reader, in the spanish literary system. This relation shows a certain realism in Villena’s writling program, which embraces the lyric bend 1971-1993. The notion of literature as system permits us see Villena’s work in a lyric bend superstamped on the so called "estética novísima" and the poetry of the ’80. The Villena’s case results interesting because of the fact that the social personage interfuses with his other textuals subjects, in front of the great public, from a television set, or from a newspaper.